Prednosti metode montessori pri obravnavi pacientov z demenco - Ljubič, Andreja (Obzornik zdravstvene nege, 2017)
Introduction: Dementia is a chronic disease with the tendency of declining patient's cognitive and mental abilities. Treatment is primarily focused on prolonging the period of independent life. Various newer complementary approaches and methods that are aimed at maintaining and encouraging cognitive abilities have been implemented across the globe. One of these methods is the approach of Maria Montessori, which has been adapted to adult persons suffering from dementia. The article presents the Montessori Method in the treatment of people with dementia and its effects on the patient's quality of life. Methods: The descriptive research methodology was used to review of domestic and foreign literature. The PRISMA method was used to review five databases accessible online and make decisions on the applicability of the reviewed sources. The conceptual model by Walker and Avant was used for data analysis. The final review included 19 studies published before May 2016. The included studies have been conducted mainly in the United States of America. Results: The three thematic areas have been identified based on reviews: (1) the effects of the Montessori-based activities on engagement and effort, (2) the impact of the Montessori-based activities on eating behaviours and (3) the benefits of the Montessori-based activities on the broader group of cognitive abilities. Discussion and conclusions: Despite the small number of publications that describe the use of the Montessori Method in the treatment of patients with dementia, the method can be represented as effective. Several authors note that this approach not only enables the preservation of cognitive and mental abilities, but even improves them.
Keywords: medicinske sestre; Montessori pedagogy; nurse; nursing; pedagogika montessori; terapevtske aktivnosti; therapeutic activities; zdravstvena nega